(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Identify some factors related to the rate of iron deficiency anemia in pregnant women coming for prenatal check-ups and making birth registration at Ha Dong General Hospital. Subject and methods: Cross-sectional study on 284 pregnant women who came for prenatal check-ups and completed antenatal records from August 1, 2024 to September 30, 2024. Results: The rate of pregnant women with iron deficiency anemia was 9.85%. The rate of pregnant women with a second child (14.14%) had significantly higher iron deficiency anemia than pregnant women with a first child (10%). 11.19% of pregnant women with a normal diet and 11.53% of pregnant women with a lower than normal diet had significantly higher iron deficiency anemia than pregnant women with increased diet during pregnancy (7.82%). Conclusion: Associated factors include inadequate iron supplementation, having a second child, and maternal diet, which are factors that increase the prevalence of iron deficiency anemia during pregnancy. Therefore, it is necessary to strengthen interventions and nutrition and health education for pregnant women to reduce anemia in this community.